PENGARUH PEMBERIAN DOSIS MIKORIZA TERHADAP PERTUMBUHAN VEGETATIF PADA TANAMAN CABAI RAWIT HIYUNG - Muhammad Maulidinor; Akhmad Rizali; Antar Sofyan (Universitas Lambung Mangkurat, 2019)
Chili Rawit Hiyung is one of the typical Chili Pepper in South Kalimantan province which is located in the village of Hiyung, Tapin Tengah District, Tapin Regency. This Hiyung Rwit Chili has been registered with the Plant Variety Protection Center and Agricultural Licensing of the Ministry of Agriculture of the Republic of Indonesia with Number 09 / PLV / 2012 dated 12 April 2012 as a Local Chili Variety by the name of Chili Rawit Hiyung. Mycorrhiza is a symbiotic association between certain fungal myceliums and high levels of plant roots. mycorrhizae have the ability to associate with almost 90% of plants consisting of agricultural, plantation, forestry, and feed crops and help increase efficiency in absorption of nutrients, especially phosphorus on marginal land. The study also had the objective of knowing the effect of mycorrhizal administration and mycorrhizal dose on vegetative growth with hiyung cayenne pepper carried out at the Wahana Borneo Institute of North Loktabat Experimental Garden, Banjarbaru using a one-factor Randomized Design (RBD), namely four mycorrhizal treatments (ie Controls, MK1, MK2, MK3 and MK4). The mycorrhizal dose given is 10 g / po; ybag, 20 g / polybag, 30 g / polybag and 40 g / pilybag. From this study the results showed that the administration of mycorrhizae had a very significant effect on the number of flowers, but did not significantly affect plant height, leaf width and many leaves.